The prediction of surface settlements due to tunnelling in soft ground - Chow, L; L. Chow (1994)
The investigation of various soil models for the prediction of surface settlement profiles due to the excavation of a single tunnel in soft ground is described in this thesis. Both analytical and numerical methods are used. Emphasis is placed on the establishment of the width of the predicted settlement trough. In the analytical analysis the ground is assumed to be an elastic halfspace. The problem is approached using two methods: (i) the application of a line load to model the uplift of soil caused by the excavation; (ii) the application of Sagaseta's method which models the soil deformation due to ground loss. For the numerical analysis of the tunnelling problem, the finite element program OXFEM is used. Finite element modelling for the simulation of tunnelling is investigated. The mesh size used in the analysis found to have an important impact on the computed results. Parametric studies using linear elastic and elastic-plastic models are carried out. The effect of stress and strain amplitudes on the behaviour of soil is also investigated. The non-linear elastic model assumes a power law between the elastic moduli and the mean effective stress, and represents the increase of stiffness with increasing stress amplitudes in the elastic region of the soil. The effect of strain amplitudes on the behaviour of soil is considered using an elastic-plastic model with nested yield loci and an outer von Mises surface. Both models have been implemented in OXFEM, and parametric studies on tunnelling are carried out using both models. Comparison between the computed results and existing empirical values of the widths of settlement troughs were carried out.